2012
DOI: 10.1186/1471-2458-12-498
|View full text |Cite
|
Sign up to set email alerts
|

Comparatively low attendance during Human Papillomavirus catch-up vaccination among teenage girls in the Netherlands: Insights from a behavioral survey among parents

Abstract: BackgroundThe Dutch Human Papillomavirus (HPV) catch-up vaccination program in 2009 appeared less successful than expected. We aimed to identify the most important determinants of refusing the vaccination.MethodsTwo thousand parents of girls born in 1996 targeted for HPV vaccination received an invitation letter to participate in a questionnaire study. Two study groups were defined: the first group consisted of parents of girls who had accepted the vaccine and already received the first dose of HPV vaccination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(78 citation statements)
references
References 13 publications
4
73
0
1
Order By: Relevance
“…Insufficient knowledge or information, and beliefs that the information available is unclear, biased and/or inadequate were identified in almost all articles reviewed. An average of 44% of hesitant participants from quantitative studies reported that there was insufficient information available about HPV vaccination, and/or that their own knowledge was insufficient, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] particularly in studies in Romania (2015, 81%), 30 the Netherlands (2009-2011, 67%), 26,28 and Denmark (2010, 70%). 35 This was also reported by 53% of general study participants [42][43][44][45][46][47][48][49][50][51] and 11% of favourable study participants.…”
Section: Quantitative Resultsmentioning
confidence: 99%
“…Insufficient knowledge or information, and beliefs that the information available is unclear, biased and/or inadequate were identified in almost all articles reviewed. An average of 44% of hesitant participants from quantitative studies reported that there was insufficient information available about HPV vaccination, and/or that their own knowledge was insufficient, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] particularly in studies in Romania (2015, 81%), 30 the Netherlands (2009-2011, 67%), 26,28 and Denmark (2010, 70%). 35 This was also reported by 53% of general study participants [42][43][44][45][46][47][48][49][50][51] and 11% of favourable study participants.…”
Section: Quantitative Resultsmentioning
confidence: 99%
“…Notably, as shown here, vaccine immunogenicity and safety studies from Asian countries show comparable outcomes to studies in other regions, including those in developed countries. For overcoming potential barriers in the area of socioeconomics, including acceptance, adherence (62,63), education and promotion of HPV-related cancer prevention should be further substantiated. Direct promotion by health-care professionals is considered as the optimal strategy (63).…”
Section: Discussionmentioning
confidence: 99%
“…In the 29 articles that studied HPV vaccination , the most common concerns identified were about safety, and particularly unknown adverse reactions that might develop long after vaccination [104][105][106][107][108][109][110]112,113,[115][116][117][118][119][120][123][124][125][126][127][129][130][131][132]. These concerns often came with discussion around the newness of the vaccine [104,107,112,113,117,126,129], and claims that it has not been tested long enough [104,105,107,115,122,[129][130][131].…”
Section: Hpv Vaccinesmentioning
confidence: 99%
“…Mistrust was common, especially of pharmaceutical companies [105,106,118,130], government [104,109,123], research [112,130], and health authorities [118,130]. Two studies reported conspiracy theories about vaccines causing sterilisation [118,130] and others expressed concerns about the vaccine not being natural [ 104,130], and a preference for homeopathy, screening or sexual abstinence [105,117,130].…”
Section: Hpv Vaccinesmentioning
confidence: 99%